2019
DOI: 10.1371/journal.pone.0212416
|View full text |Cite
|
Sign up to set email alerts
|

New tomographic contribution to characterizing mesosaurid congenital scoliosis

Abstract: The presence of a pathology in the vertebral column of the early Permian mesosaurid specimen ZPAL R VII/1, being one of the oldest amniotic occurrences of congenital scoliosis caused by a hemivertebra, was recently recognized. Here we provide CT data to further characterize the phenomenon. The affected hemivertebra is wedged (incarcerated) between the preceding and succeeding vertebrae. The neural canal is misshapen but continuous and the number of dorsal ribs on each side of the specimen corresponds with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In such cases, at least two hemivertebrae are present on opposite sides of the spine, separated by at least one normal vertebra. Hemivertebrae in a Paleozoic mesosaur ( Stereosternum tumidum ), in an ornithischian dinosaur ( Dysalotosaurus letwvorbecki ) and a temnospondyl amphibian (likely Eocyclotosaurus wellesi ) coincided with an abnormally curved vertebral column (Szczygielski et al, 2019; Witzmann, 2007; Witzmann et al, 2008). For osteichthyans, it has also been suggested that, during evolution, dorsal and ventral wedge‐shaped hemivertebrae expanded into two disks per segment (diplospondyly) that eventually fused into monospondylous vertebral centra (Starck, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, at least two hemivertebrae are present on opposite sides of the spine, separated by at least one normal vertebra. Hemivertebrae in a Paleozoic mesosaur ( Stereosternum tumidum ), in an ornithischian dinosaur ( Dysalotosaurus letwvorbecki ) and a temnospondyl amphibian (likely Eocyclotosaurus wellesi ) coincided with an abnormally curved vertebral column (Szczygielski et al, 2019; Witzmann, 2007; Witzmann et al, 2008). For osteichthyans, it has also been suggested that, during evolution, dorsal and ventral wedge‐shaped hemivertebrae expanded into two disks per segment (diplospondyly) that eventually fused into monospondylous vertebral centra (Starck, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…and a temnospondyl amphibian (likely Eocyclotosaurus wellesi) coincided with an abnormally curved vertebral column (Szczygielski et al, 2019;Witzmann, 2007;Witzmann et al, 2008). For osteichthyans, it has also been suggested that, during evolution, dorsal and ventral wedge-shaped hemivertebrae expanded into two disks per segment (diplospondyly) that eventually fused into monospondylous vertebral centra (Starck, 1979).…”
Section: Vertebral Centrum and Arch Phenotypes As Pathologiesmentioning
confidence: 99%